Analisis Kemampuan Numerasi Siswa Sekolah Dasar Fase A Dalam Mengurutkan Bilangan - Ainiyyah, Qurrotul; Sumarno, Sumarno; Dwijayanti, Ida (Polinomial : Jurnal Pendidikan Matematika, 2024)
This study aims to analyze the numeracy abilities of elementary school students in class 1 phase a. The numeracy abilities analyzed are related to the concept of numbers, namely number sequences. This analysis was carried out to determine the difficulties experienced by phase A elementary school students in the mathematics subject of ordering numbers so that teachers can plan lessons that can overcome these problems. The method used in this research is qualitative method. Data collection techniques are carried out through test and questionnaire techniques. The research data was obtained from test instruments on 13 grade 1 phase a elementary school students and questionnaire results from 10 grade 1 phase a elementary school teachers in Rembang Regency. Data analysis is presented descriptively by reducing and displaying data then verifying and drawing conclusions. The results of the analysis of numeracy skills in ordering numbers are that students have difficulty in ordering numbers from largest to smallest. This difficulty is caused because learning is not in accordance with the development of thinking of class 1 students in phase a. Learning for grade 1 elementary school students must be real in accordance with concrete operational developments. The results of the questionnaire technique in analyzing students' numeracy skills regarding ordering numbers, respondents experienced major difficulties in ordering numbers from largest to smallest either in the form of symbols or pictures. The results of the research that has been carried out show that the numeracy skills of grade 1 elementary school students in phase a in ordering numbers still encounter difficulties, namely in ordering numbers from largest to smallest. Researchers hope that there will be efforts from grade 1 teachers to plan learning strategies that contain numeracy that suit the needs and characteristics of grade 1 elementary school students.